Thoracolumbar Injury Classification and Severity Score Is Predictive of Perioperative Adverse Events in Operatively Treated Thoracic and Lumbar Fractures - Liu, Gabriel (KOREAN SOC SPINE SURGERY, 2024)
10.31616/asj.2021.0231